Model PAIKEM dengan Jeopardy: Dampaknya pada Hasil Belajar Siswa pada Materi Gelombang Bunyi - Ramdhani, Ilham; Rizal, Rahmat; Maulidah, Rifa'atul (Jurnal Pendidikan dan Ilmu Fisika, 2025)
A preliminary study at a school in Tasikmalaya revealed that conventional, monotonous learning methods led to low student activity and poor learning outcomes in sound wave material. To address this, researchers explored the PAIKEM (Active, Innovative, Creative, Effective, and Fun Learning) model using the Jeopardy game. This quasi-experimental study employed a Matching Only Posttest-Only Control Group Design with purposive sampling in two classes: one experimental and one control. Data were collected using a non-test instrument (observation sheet) and a test instrument (validated descriptive test with 8 questions). Hypothesis testing using a t-test at  significance level showed  ( ), indicating  was rejected and  accepted. This confirms that the PAIKEM model integrated with the Jeopardy game positively affects students’ cognitive learning outcomes on sound waves. The findings suggest that this model can help teachers enhance student engagement and improve learning outcomes.